Production of cold-smoked skinless paiche (Arapaima Gigas, Cuvier 1829) fillets - Roldán-Acero, David Julián (2020)
This work aimed to produce cold-smoked skinless paiche fillets that comply with the quality, safety and acceptability standards regarding physical, chemical and microbiological aspects. The production stages were reception, washing, slicing and cutting, brining, draining, smoking, chilling, packaging, freezing and storage. The results showed that cold-smoked skinless paiche fillets had 75.10% moisture and 35.65% of 2.90% sodium chloride. The fillets had 20.0% protein, 2.5% fat and 2.4% ash. The total energy per 100 g of fish was 102.5 kcal. The microbiological results of the cold-smoked fillets met the recommended quality standards for this type of product, and confirmed that good manufacturing practices were used during their production.